Review on Automotive Body Coating Process - Prof. Mahajan S.M; Varade Mayur A; Mahajan Pratiksha N; Patil Sneha V (International Journal of Engineering and Management Research, 2019)
Automotive coatings and the processes used to coaat automobile surfaces exemplify the avant-grade of technologies that are capable of producing durable surfaces, exceeding customers expections of apperance, maximizing efficiency, and meeting environmental regulations. These accomplishments are rooted in 100 years of experience, trial-and-error approaches, technique and technology advancements, and theroetical assessments. Because of advancenments directed at understanding the how, why, when, and where of automobile coatings, the progress in controlling droplets and their deposition attributes, and the development of new technologies and paint chemistries, a comprehensive and up-to-date review of automobile coating and coating technologies was considered to be a value to industrial practitioners and researches. Overall the critical performance factors driving the development and use of advanced automotive coatings and coating technologies are (a) aesthetic characteristics; (b) corrosion protection; (c) mass production; (d) cost and environmental requirements; (e) appearance and durability. Although the relative importance of each of these factors is debatable, the perfection of any one at the expense of another would be unacceptable. Hence, new developments in automotive coatings are described and discussed in the following review, and then related to improvements in production technologies& paints. Modern automotive coating procedure are also discussed in details.